Thermal performance and heat flux dynamics of electrically heated windows: a foundation for energy-efficient active glazing systems - Koshlak, Hanna (International Conference “Environmental Engineering”, 2026)
The building sector remains a primary contributor to global energy consumption, with windows often iden-tified as the least efficient component of the building envelope. This study investigates the thermal performance of an“active” smart window system featuring an integrated electrical heating element within the glazing cavity. Experimental trials were conducted in a specialised dual-zone climatic chamber to evaluate the heat flux dynamics and surface temperature distributions of a heated triple-glazed unit (TGU) compared to a standard reference unit. High-precision thin-film heat flux sensors and calibrated thermocouples were utilised to quantify thermal transfer across an external temperature range of −25 °C to +5 °C. The results demonstrate that precise modulation of the heating power enables the achievement of a “near-zero thermal balance,” effectively transforming the window from a thermal bridge into a thermally neutral element. While active heating elevates the external glass surface temperature, leading to increased external heat dissipation, it simultaneously mitigates the “cold pane” effect and enhances indoor radiant comfort. The findings suggest that the positive thermal effect on the indoor environment can outweigh external losses, particularly when managed as a demand-responsive system. The study concludes that integrating active glazing with renewable energy technologies, such as semi-transparent photovoltaics, offers a viable pathway toward achieving Net Zero Energy Building (NZEB) standards by providing a self-powering, high-performance architectural solution.
Keywords: active glazing; electrically heated windows; heat flux density; thermal comfort; energy efficiency; smart buildings; net-zero thermal balance; NZEB